Variation in folklore and language - Babič, Saša; Voolaid, Piret (Cambridge Scholars Publisher, 2019)
Variation is a universal phenomenon permeating language, culture, and entire worldviews. This book analyses issues related to both specific and common variations in folklore and language as signifiers of culture and worldview. The articles here are dedicated to different genres and forms, including spoken and written language, dancing and singing, and festivities, and involve different aspects of variation. Variation is conceptualised here as the main basis of folklore dynamics and a major issue of typology. A significant part of the volume is dedicated to variations of myths and motifs, creat.